Social Media as a Tool for Improving English Proficiency Among Students of the Shehu Sule College of Nursing Sciences Damaturu - Adamu Abubakar Muhammad; Bello Muhammad Jajere; Rabi Yusuf Adamu (Journal of English as A Foreign Language Teaching and Research, 2025)
This study explores the role of social media in enhancing English proficiency among students at the Shehu Sule College of Nursing Sciences, Damaturu. Despite the growing use of digital platforms in education, limited research has examined their specific impact on language learning in this context. This study addresses this gap using a quantitative approach by distributing an online questionnaire via college students’ WhatsApp groups. A total of 104 students participated in the study, and data were analyzed using descriptive statistics and frequency distribution. Google Docs spreadsheets were used for chart visualization. Findings reveal a gender disparity, with 79.8% of male and 20.2% of female respondents. The frequency of social media usage varied, with 42.3% using it daily, 36.5% several times a week, 18.3% occasionally, and 2.9% infrequently. WhatsApp was the most preferred platform (42.4%), followed by Facebook (20.7%), YouTube and Instagram (17.4% each), and TikTok (2.2%). Key learning activities included watching educational videos (28.0%), following language-learning groups (26.2%), reading posts (20.9%), and language exchanges (14.2%), while podcast listening was less common (10.7%). Students reported improvements in vocabulary (41.4%), grammar (50.0%), and pronunciation (55.7%), with 47.2% experiencing increased motivation. Additionally, 70.2% of respondents support integrating social media into formal education, while 21.2% advocate a cautious approach. The study recommends promoting female engagement, developing tailored learning resources, incorporating emerging platforms, enhancing interactive activities, and formally integrating social media into English curricula. These findings underscore social media’s potential as an effective supplementary tool for language learning.